Bio-Preparation of Iron Nano Fertilizers from Lemon Fruit Affected some of the Characters of Carrot plants (Daucus carota L.) - Laila Hefdah Allah Alansi; Najeeb M. Al-Magrebi Al-Magrebi (مجلة ديالى للعلوم الزراعية)
To study the biological preparation of iron nano fertilizers from lemon fruit extract and their effect on some quantitative traits of carrot (Daucus carota L.) plant. Experiments were conducted, a laboratory part and a field part, with two addition factors, foliar fertilization and soil fertilization, using two sources of iron. The first source was nano-iron at a concentration of 0.5, 1, 1.5, and 2 mg L-1, and the second source was chelated iron at a concentration of 1.5 g L-1 and control treatment. The results showed the superiority of foliar fertilization in most of the studied traits such as iron concentration, root length, root diameter, fresh weight, dry weight, carotene and total dissolved solids (144.30 ppm, 17.10 cm, 2.1 cm, 137.98 g, 16.03 g, 1.62 mg g fresh weight-1 and 8.79 %, respectively). Nano-iron spraying was superior than to chelated iron in the concentration of iron (Fe), root length, root diameter, fresh weight, dry weight, and total dissolved solids (1059.22 ppm, 20.82 cm, 2.29 cm, 168.97 g, 18.37 g, and 9.91 %, respectively). X-ray diffraction (XRD) was used to determine the size and purity of the nanoparticles, and scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) were used to verify the composition. Iron oxide (Fe2O3) was in the form of α-Fe2O3 hematite with a size of 32.8 nm and Ỵ-Fe2O3 maghematite with a size of 44.6 nm. We conclude that the use of green synthesis method for nano-fertilizers has proven effective and efficient from an economic and environmental point of view.